2016
DOI: 10.1007/s11207-016-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Oscillations in a Coronal Loop Triggered by a Jet

Abstract: We detect and analyse transverse oscillations in a coronal loop, lying at the south east limb of the Sun as seen from the Atmospheric Imaging Assembly (AIA) onboard Solar Dynamics Observatory (SDO). The jet is believed to trigger transverse oscillations in the coronal loop. The jet originates from a region close to the coronal loop on 19th September 2014 at 02:01:35 UT. The length of the loop is estimated to be between 377-539 Mm. Only one complete oscillation is detected with an average period of about 32 ± 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Using the magneto-seismology technique, the measured oscillation parameters could be used to derive the magnetic field strength of the loops/filaments. For example, Sarkar et al [225] reported a case of jet-driven transverse oscillation of a coronal loop whose magnetic field strength was estimated to be about 2.68-4.5 Gauss. Luna et al [214] estimated the minimum magnetic field strength of an oscillating filament to be about 14 Gauss.…”
Section: (C) Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…Using the magneto-seismology technique, the measured oscillation parameters could be used to derive the magnetic field strength of the loops/filaments. For example, Sarkar et al [225] reported a case of jet-driven transverse oscillation of a coronal loop whose magnetic field strength was estimated to be about 2.68-4.5 Gauss. Luna et al [214] estimated the minimum magnetic field strength of an oscillating filament to be about 14 Gauss.…”
Section: (C) Magnetohydrodynamic Wavesmentioning
confidence: 99%
“…Besides the ordinary collimated motions, jets often exhibit helical structure and untwisting motions (Shen et al, 2011;Shen et al, 2012). In addition to helical and untwisting motions, jet displays the swaying motions (transverse oscillations) (Sarkar et al, 2016). Jets may also be formed by shock waves (e.g., De Pontieu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Catalogs of observations have been produced by Zimovets and Nakariakov (2015) and . Kink oscillations attract a lot of attention due to their potential for seismological studies of the coronal plasma (e.g., reviews by De Moortel and Stepanov et al, 2012;Pascoe, 2014;De Moortel et al, 2016), in particular to estimate the strength of the coronal magnetic field (e.g., Nakariakov et al, 1999;Nakariakov and Ofman, 2001;Van Doorsselaere et al, 2007;White and Verwichte, 2012;Pascoe et al, 2016;Sarkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%